1998
DOI: 10.3109/10428199809058382
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Myeloid and Lymphoid Development of Hematopoietic Stem Cells by Bone Marrow Stromal Cells

Abstract: Development of hematopoietic stem cells is regulated by stromal cells of the bone marrow. Many stromal cell lines have been established from temperature-sensitive SV40 large T-antigen gene transgenic mice and used to examine regulation of the purified stem cells. When the sorted stem cells were cocultured on the stromal cell layers, cobblestone formation was induced by the stromal cells. The cobblestones were formed by finite cell division (8 divisions on average) of sorted Lin- c-Kit+ Sca1+ stem cells committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…With the exception of myelofibrosis [30] hardly anything is known about the other constituents of the bone marrow stroma responsible for the complex functional network composing the microenvironment, which exerts a significant impact on haematopoietic recovery and differentiation [23]. In this elaborate concert of various cell-to-cell and stromal matrix interactions, the resident macrophages deserve special attention.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of myelofibrosis [30] hardly anything is known about the other constituents of the bone marrow stroma responsible for the complex functional network composing the microenvironment, which exerts a significant impact on haematopoietic recovery and differentiation [23]. In this elaborate concert of various cell-to-cell and stromal matrix interactions, the resident macrophages deserve special attention.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In addition, stromal cells, cytokines, receptors, ligands, signaling molecules, and transcription factors have been shown to affect levels of B and T lymphocytes. [7][8][9][10] Previous studies identified molecular factors that play important roles in the regulation of B-and T-cell commitment and balance such as cytokines interleukin-3 (IL-3) and IL-7, signaling receptor and ligand Notch and Jagged, paired-box gene Pax5, and the transcriptional factors E2A and EBF. 3,[11][12][13] Mutations that change the relative levels of other leukocyte subsets may also indirectly affect B-and T-cell proportions.…”
mentioning
confidence: 99%
“…The second hypothesis on IFN action regards the fibrous interstitial matrix because several groups have shown definite alterations in the adhesive properties of CML progenitor cells to the marrow stroma layer. This pathomechanism may be responsible for the abnormal situation of a continuously occurring proliferation and differentiation of a (leukemic) cell population (44 -46) that is not subjected to the regulatory influences of the functionally complex modulation by the microenvironment (15,16). In this regard, IFN may act by correcting the defective adhesion to the bone marrow stroma, which in turn restores normal regulation of progenitor cell maturation and thus restitution of non-clonally transformed hematopoiesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the paucity of lymphocytes within the hematopoietic tissue has significantly hampered any investigations attempting to elucidate alterations during chemotherapy or interferon administration. In vitro studies are in keeping with the assumption that the bone marrow stromal cells selectively induce a lineage-specific commitment of the myeloid and lymphoid progenitors (15,16). One of the effects of interferon-␣ (IFN) is to restore non-clonally transformed hematopoiesis in CML by a restitution of normal responsiveness to the negative regulation of the microenvironment (17)(18)(19).…”
mentioning
confidence: 91%